2006
DOI: 10.1124/mol.106.028449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Antiproliferative Effect of Agmatine in Tumor Cells of Colonic, Hepatic, and Neuronal Origin

Abstract: The aim of the present study was to challenge potential mechanisms of action underlying the inhibition of tumor cell proliferation by agmatine. Agmatine inhibited proliferation of the human hepatoma cells HepG2, the human adenocarcinoma cells HT29, the rat hepatoma cells McRH7777, and the rat pheochromocytoma cells PC-12. Inhibition of proliferation of HepG2 cells was associated with an abolition of expression of ornithine decarboxylase (ODC) protein and a doubling of mRNA content encoding ODC. In HepG2 cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…It has been reported that the overexpression of ODC may lead to increased polyamine levels and thus induce the overproliferation and malignant transformation of cells (4,(16)(17)(18)(19). It contributes to the development, progression, metastasis and surrounding invasion of malignant tumors, and serves as a useful biological marker for certain precancerous lesions of digestive malignancies (4)(5)(6)(7)(8)16,17,20). A previous study demonstrated that Helicobacter pylori upregulates the expression of ODC, resulting in gastric precursor lesions and cancer (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the overexpression of ODC may lead to increased polyamine levels and thus induce the overproliferation and malignant transformation of cells (4,(16)(17)(18)(19). It contributes to the development, progression, metastasis and surrounding invasion of malignant tumors, and serves as a useful biological marker for certain precancerous lesions of digestive malignancies (4)(5)(6)(7)(8)16,17,20). A previous study demonstrated that Helicobacter pylori upregulates the expression of ODC, resulting in gastric precursor lesions and cancer (21).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas with highly expressed ODC are more progressive and poorly differentiated, with increased metastasis, surrounding invasion and poor prognosis. Hence, ODC may be a novel target for use in the development of new anticancer drugs and as an indicator for the efficacy of treatments (4)(5)(6)(7)(8)16,17,20). Tissue-specific markers are useful for the identification of tumor type in advanced cancers of unknown origin.…”
Section: Discussionmentioning
confidence: 99%
“…Both RNA and cDNA concentrations were determined spectrophotometrically (Biorad Spectronanodrop). The primer sequences included sense 5'-ATTGTTCCGTTCTTCTTGACTT-3' and antisense 5'-AGTGTGATGTGAAGGATTATG-3' for ARG1 (148bp), sense 5'-GGTCCCGCTGCCATAAGAG-3' and anti-sense 5'-CGTGGATTCACTATCAGGTTGTTG-3' f o r A R G 2 ( 1 3 7 b p ) , s e n s e 5'-GGATCCAAATGTGGCTGCGTTCAT-3' and antisense 5'-AACAGCCAGCCATCTACCAGTTCT-3' f o r O A T ( 1 7 5 b p ) , s e n s e 5'-GTGGGTGATTGGATGCTCTTTG-3' and anti-sense 5'-AGGCCCTGACATCACATAGTAG-3' for ODC (108bp), sense 5'-GAAATCCCATCACCATCTTCC-3' and anti-sense 5'-GAGCCCCAGCCTTCTCCATG -3 ' f o r G A P D H ( 1 2 0 b p ) , a n d s e n s e 5'-TGGATCAGCAAGCAGGAGTATG-3' and antisense 5'-AAGAAAGGGTGTAACGCAACTAAG-3' for β-actin (98bp) (Bergeron et al, 2007;Wolf et al, 2007;Haenisch et al, 2008;Kitowska et al, 2008;Kim et al, 2012;Mondal et al, 2013). For all analysis, sqPCR assays were performed in a 25 µL system containing PCR master mix, 30ng first-strand cDNA template and 0.4 µM appropriate primers.…”
Section: 7031 Modulation Of L-arginine-arginase Metabolic Pathway Enmentioning
confidence: 99%
“…The ability of Arg to inhibit the tumor growth based on the metabolism of Arg or based on its chemical structure has been verified and confirmed. Arg when incubated in medium for 24-72 h had been shown to kill gastric cancer cells through apoptosis based on the metabolism of Arg [7,8]. Yurtcu et al [4] have reported also that based on the metabolism Arg could induce DNA damage with rising of NO in lymphocytes.…”
Section: Introductionmentioning
confidence: 99%